Editorial - Chau, Meng Huat (Journal of Modern Languages, 2021)
Welcome to the first issue of the Journal of Modern Languages in 2021. During this tumultuous time across the globe, we are particularly humbled by and grateful for the generosity and support of our learned community. Despite the ongoing pandemic, contributors have been patient and productive, and we are on track to receive a good number of submissions for this issue. The review process has taken a bit longer than usual for some submissions as we have given reviewers extra time due to the extra stress everyone is facing these days. As in the past two years, we are pleased to publish six full-length articles in this issue. It features an excellent range of language and multimodal investigations. Readers will find such diverse sites of analysis as newspapers, poetry book, and hippie and punk concert posters. This is an encouraging sign for the Journal, and we would like to see more varied explorations and geographic diversity among submissions to be published in this Journal. We would also like to gently remind readers of the multilingual and multicultural nature of our Journal: we are interested in and encourage studies of all languages, not just English. The Journal of Modern Languages, like all other scholarly journals, depends on the support of individuals from a range of areas in modern language studies. The insightful comments and suggestions of reviewers allow the Journal to maintain the high quality of the articles. The number of submissions we receive for consideration of publication steadily increases each year. As a result, we need more and more external reviewers. If any readers of the Journal would like to be external reviewers, please contact us with an indication of the areas in which you have particular expertise. We hope that you will enjoy reading this issue of the Journal of Modern Languages. All of us involved in the publication of this Journal wish our readers and their families good health and many blessings.